STUDY OF REACTION KINETICS ON BIODIESEL PRODUCTION USING IN SITU METHOD WITHOUT CATALYST - Naulina, Rosada Yulianti; Hendratama, Handik; Nury, Dennis Farina; Zullaikah, Siti (World Chemical Engineering Journal, 2023)
Biodiesel from rice bran using an uncatalyzed in-situ transesterification method in subcritical ethanol - water has been investigated. This method is known to be economical because the experimental steps are reduced and environmentally friendly because we do not use a catalyst. In this experiment, CO2 was used as a compressed gas and ethyl acetate as a co-solvent to increase yield. This reactor is equipped with a stirrer that uses a magnetic stirrer. Rice bran, a mixture of water, ethanol and ethyl acetate in a mole ratio of 1:10:9:2 is fed into the reactor, then injecting CO2 gas to increase the pressure and to ensure the reaction takes place under subcritical conditions under operating pressure of 80 bar.Temperature (120 - 200ᵒC) and reaction time (1 - 4 hours) were investigated to increase biodiesel. The highest yield of FAEE composition at 200ᵒC for 3 hours was 91.264% with the results of calculating the kinetics of the transesterification reaction, the values of k1 and k2 were 0.349.10-3 and 0.0045 mL3.mmol-3.min-1. Meanwhile, in the esterification reaction, the values for k1 and k2 were 0.0194 and 0.0579 mL3.mmol-3.min-1.